A document tracking web-based system of student activity HEP UiTM Shah Alam / Mohd Adi Shahzaley Salleh - Salleh, Mohd Adi Shahzaley (2020)
The Student Affairs Department is one of the most important departments at University Technology MARA (UiTM). It is specifically set up to provide service for the welfare of students. The club and societies of students are managed through the Student Activity Center. However, this department does not have any technology system to manage the document tracking of student activity request. The document was submitted by face to face between the student and staff. To make relevant improved the document tracked, it is possible to track through a system instead of document sent manually. This system was implemented with functioning in created, viewed, updated and deleted data from the database. As a result, after the student generate form and upload the document to the system, the document stored at the database. The data updated and viewed by the staff. The document has downloaded by staff and has to update the status of document. So that, the status of document viewed by the student through system. As conclusion, document tracking through web based is one of the technique that can be used to give a solution for services and to make this services faster, effectively and enhanced in future development.